The Association between Aspect of Family Communication Dimentions Beforehand, To, and Throughout The COVID-19 Pandemic - Wulandari, Maulina Pia; Amanda, Fakhirah (Jurnal Ilmu Komunikasi, 2023)
The COVID-19 pandemic resulted in the Indonesian government implementing work-from-home and Distance Learning (PJJ) regulations that affect how people communicate with others, how close they feel to each other, and how they resolve family problems. This research aims to analyze the different types of communication within the family that influence the level of closeness and differences of opinion before, during, and after the COVID-19 pandemic. This research uses quantitative research methods, collecting data through survey questionnaires and using Statistical Structural Equation Modeling(SEM) as the primary technique for data analysis. The results of this study show substantial changes in communication and conflict patterns in families before and after the COVID-19 pandemic. In addition, no significant differences were found before and during the pandemic in the relationship between family communication patterns and family intimacy, as well as between family intimacy and family conflict. Family intimacy is essential in mediating the relationship between family communication patterns and conflict. This study shows that increasing levels of family communication, characterized by a lack of understanding of the roles of individual family members and a focus on dialogical communication and equality, can give rise to disputes that weaken unity and harmony within the family unit. This research contributes to the field of family communication theory by showing the impact of external circumstances, such as a pandemic, on internal family dynamics.